Deubiquitinase Inhibitors Impair Leukemic Cell Migration Through Cofilin Oxidation and Alteration of Actin Reorganization - Larbret, Frédéric; Biber, Pierric; Dubois, Nicholas; Ivanov, Stoyan; Lafanechere, Laurence; Tartare-Deckert, Sophie; Deckert, Marcel (Frontiers in Pharmacology, 2022)
Actin networks are dynamically regulated through constant depolymerization and polymerization cycles. Although the fundamental mechanisms that govern these processes have been identified, the nature and role of post-translational modifications (PTMs) of actin and actin regulatory proteins are not completely understood. Here, we employed Actin CytoFRET, a method that we developed for real time detection of fluorescence resonance energy transfer (FRET) signals generated by actin dynamics, to screen a small library of PTM-interfering compounds on a biosensor leukemic T cell line. This strategy led to the identification of small molecule inhibitors of deubiquitinating enzymes (DUBs) as potent inducers of actin polymerization and blockers of chemotactic cell migration. The examination of the underlying mechanism further revealed that the actin depolymerizing protein cofilin represents a major effector of DUB inhibitor (DUBi)-induced actin reorganization. We found that DUB blockade results in the accumulation of polyubiquitinated proteins and ROS production, associated with cofilin oxidation and dephosphorylation on serine 3, which provokes uncontrolled actin polymerization impairing cell migration. Together, our study highlights DUBs as novel regulators of actin dynamics through ROS-dependent cofilin modulation, and shows that DUBi represent attractive novel tools to impede leukemic cell migration.